Retrospective radiological evaluation to study the prevalence and pattern of maxillofacial fracture among Military personal at Prince Sultan Military Medical City [PSMMC], Riyadh: An institutional study - Zayed Ali Assiri; Ra'ed Ghaleb Salma; Emtenan Abdulrahmman Almajid; Alia Khalid Alfadhel (Elsevier, 2020)
Purpose: The aim of the present study was to analyze the prevalence, causes, and patterns of maxillofacial fractures retrospectively in patients who were treated at Prince Sultan Military Medical City, Riyadh, Saudi Arabia. Methods: Patients' medical records were reviewed from 2005 to 2014. Patient's age, gender, cause, and the pattern of maxillofacial fractures were studied. Associated body injuries were also recorded. Results: Out of 263 patients, 207 (78.7%) were male and 56 (21.3%) were female. The age range was from 3 to 67 yr with a mean age of 26.21 yr. Road traffic accidents 236 (89.8%) were the most commonly reported cause of maxillofacial fractures, followed by falls 14 (5.3%), assaults 4 (1.5%), gunshot 3 (1.1%), and sport accidents 2 (0.8%). Most of the cases of maxillary fracture were Le Fort II 27 (36.5%), followed by LeFort I 23 (31.1%), LeFort III 20 (27.0%) and palatal fractures 4 (5.4%). Of the mandibular fractures, parasymphysis fractures constituted 61 (27.4%), body 50 (22.4%), condyle 45 (20.2%), angle 40 (17.9%), symphysis 16 (7.2%), ramus 7 (3.1%) and coronoid 4 (1.8%). Zygomatic complex fractures 110 (94.8%) were the most commonly reported fractures in the mid and upper facial region. Other facial fractures included orbital floor 61 (97.0%), naso-orbito-ethmoidal 18 (19.8%), and frontal 12 (13.2%). Conclusion: Road traffic accidents were the most common cause of maxillofacial fractures. Spreading awareness among young drivers regarding road safety regulations is highly recommended.